Pengenalan Kajian Ergonomis Terhadap Desain Produk Untuk Mengembangkan Kompetensi Belajar Siwa SMK Muhammadiyah I Temon Kulon Progo - Poerwanto, Eko (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2019)
Industry 4.0 requires creative and innovative human resources so that the products design competency of ergonomic is an important requirement for the demands of customized products. Muhammadiyah I Vocational School Temon, Kulon Progo district is a vocational school that is very close to the new International Airport for Yogyakarta, so it is a very strategic activity to provide an introduction to the Aviation Industry and Ergonomics in Product Design. This is important to provide provision for students of vocational school to be able to know the requirements and standards of service products / goods so that they can be accepted in the Aviation Industry. The results of observations in the field show that most students' understanding of HR standards for the Aviation Industry is still very lacking and understanding ergonomics in product design is still very lacking.